Manajemen Perioperatif pada Pasien dengan Hipertensi: Tinjauan Pustaka - Khoirul Basyar, Fragil; Subekti, Bambang Eko (CV. Jasa Sukses Abadi, 2026)
Hypertension is a chronic condition characterized by sustained elevation of blood pressure ≥130/80 mmHg and is one of the major risk factors for morbidity and mortality among patients undergoing elective surgery. Globally, hypertension affects more than 1.13 billion individuals and contributes to approximately 9 million deaths annually. Despite advancements in antihypertensive therapy, hypertension remains a significant clinical challenge in perioperative management. Meta-analyses indicate that hypertension increases the risk of postoperative cardiovascular complications by up to 35%, underscoring the importance of effective perioperative management. Blood pressure regulation involves baroreceptor reflex mechanisms and the Renin–Angiotensin–Aldosterone System (RAAS). Dysregulation of these systems influences hemodynamic responses during anesthesia, in which reduced sympathetic activity and increased RAAS activation may elevate the risk of intraoperative hypotension, particularly in patients receiving specific classes of antihypertensive medications. Perioperative management begins with a comprehensive blood pressure assessment. Surgical delay is recommended only in cases of severe hypertension, defined as diastolic pressure >110 mmHg, or when significant comorbidities are identified. Management of antihypertensive medications plays a crucial role. Angiotensin-Converting Enzyme Inhibitors (ACEIs) and Angiotensin II Receptor Blockers (ARBs) are generally recommended to be withheld 24 hours prior to surgery to prevent intraoperative hypotension, except in stable heart failure patients. Large cohort studies have demonstrated that discontinuing ACEIs/ARBs before surgery reduces the composite risk of mortality, stroke, and myocardial injury in non-cardiac procedures. In contrast, β-blockers should be continued until the day of surgery, as abrupt discontinuation may induce rebound hypertension, tachycardia, and an increased risk of myocardial ischemia. Meta-analyses show that β-blockers effectively reduce the incidence of postoperative myocardial infarction and arrhythmias. Perioperative management in hypertensive patients requires an individualized approach that considers clinical status, medication profile, and hemodynamic risks associated with anesthesia.